Agents of transition or defenders of the status quo? Trade union strategies in green transitions. (September 2022) - Kalt, Tobias
Green transitions create major challenges to union power in carbon-intensive economies as well as opportunities for the renewal of union power. This research asks why sometimes unions oppose or delay green transitions while other times unions are more open to green transitions and may even become strong transition supporters. In drawing on the Power Resource Approach, I argue that unions are neither natural opponents nor supporters of green transitions but instead engage strategically with green transitions. Unions' strategic choices to pursue oppositional, reactive, affirmative or transformative transition strategies is guided by an imperative to maintain or expand their power resources. The strategic choices unions make are influenced by several contextual conditions. In a comparative case study on coal transitions in South Africa and Germany, I identify the following contextual conditions: sectoral interests, organisational identity, internal structure, coalitions, political- and socio-economic environment, governance context and public discourse. Regarding each of these, I show how unions make strategic choices to protect or expand different power resources and become agents of transition or defenders of the status quo. This paper contributes to empirical research on drivers behind union transition strategies and offers an analytical framework to explain unions' strategic choices in green transitions.